The Effect of 4-2 Training Using Two Touches on Passing Skills and Shooting Ability in Mandalika FC U-17 Football - Maulana Husairi (Jurnal Pengetahuan dan Pendidikan, 2024)
In football, one of the most dominant basic techniques used is passing. Passing in football aims to pass the ball to teammates in order to create space, so that players can score goals against the opponent's goal and can maintain the defense area for defenders. The purpose of this study was to determine the effect of the 4-2 training model using two touches on the passing and shooting skills of Mandalika FC U-17 football athletes. This study is a quasi experiment. The design used in this study is "Two Group Pretest Posttest Design" Experimental method with non-separate samples means that researchers only have one group. The results of the study showed that some children's lower passing abilities increased drastically, some even decreased their abilities. This is because this type of research is a quasi experiment, meaning that researchers cannot fully monitor children's activities outside the training/treatment schedule given by researchers. It is possible for children whose abilities have increased drastically because the child also continues to practice outside the training/treatment schedule given by researchers. While for children whose abilities have decreased, it is possible that the child did not take the training seriously, and there were also children who were sick at the time of posttest data collection so that their abilities were not optimal. that there is a significant effect of paired passing training on the ability of underhand passing of Mandalika fc. u-17 football school students, the t-value is 6.574> t-table 2.09, and the significance value is 0.000 <0.05, and the percentage increase is 37.69%.